Asexual propagation of blackbrush (Coleogyne ramosissima Torr.) - Weglinski, Eugene, author; Hughes, Harrison G., advisor; Redente, Edward F., committee member; Orr, Greg L., committee member (Colorado State University. Libraries, 1990)
Mining disturbances in Canyonlands National Park occur, in part, in monotypic stands of blackbrush (Coleogyne ramosissima Torr.). Blackbrush does not readily reseed itself following disturbance, therefore, stem cuttings and mound layering were evaluated as methods for asexual propagation as a means of providing plants to be used in a revegetation program. Rooted cuttings were planted to evaluate their use in revegetation. Rooting of stem cuttings was evaluated using talc, 0.3% (w/v) indole-3-butyric acid (IBA), 0.8% (w/v) IBA, and Rootone, a commercially available rooting hormone mixture. Treatments were applied to cuttings collected from new, one-year-old, and older wood (2+ years) at three separate dates. Propagation by stem cutting proved successful with highest rooting percentages achieved using current year's growth with application of supplemental rooting hormone. Differences between hormone treatments were insignificant. However, differences were found in comparisons between hormone treatments and a talc control. Mound layering was investigated with 20 plants at each of three sites and involved removal of all growth over 2.5 cm above ground level. Supplemental water was applied to half the plants for the duration of the study. Plants were buried to one-half of the height of new growth on a monthly basis. Plants responded to the treatment with a flush of growth but did not root. Thirty-eight cuttings rooted the prior year were planted in spring 1989 in an abandoned roadbed to evaluate field establishment. Treatments included application of supplemental water at two week intervals. Results were inconclusive.
Covers not scanned.
Keywords: Plant propagation; Revegetation; Reclamation of land